A longitudinal study of parent‐reported sensory responsiveness in toddlers at‐risk for autism. (23rd October 2018) - Wolff, Jason J.; Dimian, Adele F.; Botteron, Kelly N.; Dager, Stephen R.; Elison, Jed T.; Estes, Annette M.; Hazlett, Heather C.; Schultz, Robert T.; Zwaigenbaum, Lonnie; Piven, Joseph; ,
Abstract : Background: Atypical sensory responsivity and sensory interests are now included in the DSM 5 diagnostic criteria for autism spectrum disorder (ASD) under the broad domain of restricted and repetitive behavior (RRB). However, relatively little is known about the emergence of sensory‐related features and their relation to conventionally defined RRB in the first years of life. Methods: Prospective, longitudinal parent‐report data using the Sensory Experiences Questionnaire (SEQ) were collected for 331 high‐risk toddlers (74 of whom met diagnostic criteria for ASD at age 2) and 135 low‐risk controls. Longitudinal profiles for SEQ scores were compared between groups across ages 12–24 months. Associations between SEQ measures and measures of RRB subtypes (based on the Repetitive Behavior Scale, Revised) were also examined. Results: Longitudinal profiles for all SEQ scores significantly differed between groups. SEQ scores were elevated for the ASD group from age 12 months, with differences becoming more pronounced across the 12–24 month interval. At both 12 and 24 months, most measures derived from the SEQ were significantly associated with all subtypes of RRB. Conclusions: These findings suggest that differences in sensory responsivity may be evident in high‐risk infants later diagnosed with ASD in early toddlerhood, and that the magnitude of these differences increases over the second year of life. The high degree of association between SEQ scores and RRB supports the conceptual alignment of these features but also raises questions as to explanatory mechanisms.